2019
DOI: 10.1002/poc.4026
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene‐based fluorescent supramolecular hydrogel: scaffold for nanoparticle synthesis

Abstract: The present work illustrates the design and development of pyrene-based fluorescent supramolecular hydrogel consisting of L-phenylalanine residue as the linker and ethyleneoxy unit with free primary amine at C-terminal. The gelator efficiently immobilized aqueous media, and the critical gelation concentration (CGC) was found at 2.8 mM of the compound. Interestingly, the presence of pyrene moiety in the structure made the hydrogel intrinsically fluorescent.The self-aggregation properties of the thermo-reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…12c). 41 The ambidextrous gelator ( 29) was an efficiently gelatinized organic solvent as well as aqueous media at suitable pH. The crucial role of the HLB in self-assembled gelation was studied by the sensible alteration of the amino acid residue present in the gelator.…”
Section: Pyrene-based Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…12c). 41 The ambidextrous gelator ( 29) was an efficiently gelatinized organic solvent as well as aqueous media at suitable pH. The crucial role of the HLB in self-assembled gelation was studied by the sensible alteration of the amino acid residue present in the gelator.…”
Section: Pyrene-based Gelmentioning
confidence: 99%
“…(b) Self-assembly of perylene bisimides hydrogels (40). (c) Structure of perylene bisimide organogels (41). (d) Self-assembly of multi-stranded perylene dye (42).…”
Section: Perlylene-based Gelmentioning
confidence: 99%
“…These bands could be identified as the N−H stretching, the CO stretching of carboxyl, the amide I band (1660 and 1640 cm −1 ), and the amide II band, respectively. 33,65 The black line in Figure 3d is the spectrum of the PyFF powder, and its corresponding bands shifted to 3294, 1633, and 1541 cm −1 in comparison to the band of the aerogels. Therefore, the blueshifts (3285 to 3294, 1538 to 1541 cm −1 ) and the redshift (1640 to 1633 cm −1 ) of characteristic peaks could be identified as a difference in the strength of the hydrogen bonding interactions in the two states.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Kar et al, reported the in situ synthesis of 25–40 nm silver nanoparticles by irradiating with sunlight a hydrogel containing AgNO 3 without an extrinsic reducing agent. The gelator, PyPheAla, was comprised of pyrenyl and L-phenylalanine substituents ( Figure 29 ) [ 34 ]. A 5.6 × 10 −4 mM solution of PyPheAla in water upon excitation at 340 nm emitted strongly at 376, 395 and 417 nm, indicative of emission from a pyrenyl monomer.…”
Section: Mechanical and Other Perturbations On Emitting Gelsmentioning
confidence: 99%
“…In this way, they can be thermo-reversible, thixotropic, acid-base sensors, etc., in ways that affect their luminescent properties. As a result, these gels have been studied widely for applications in diverse fields, such as excitation energy transfer and light harvesting [ 23 , 24 , 25 , 26 ], dye-sensitized solar cells [ 27 ], sensing of metal ions and explosives [ 28 , 29 , 30 , 31 ], acid and base sensing [ 32 , 33 ], and as templates for nanoparticle synthesis [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%